Decision-Making preferences in advanced cancer patients: associations with sociodemographic and psychological factors - Caterina Calderon; Ana Fernández-Montes; Marina Gustems; Lucia Roncero; Jesús Peña-López; Elena Asensio-Martínez; Mar Muñoz-Sánchez; Paula Jimenez-Fonseca (BMC Palliative Care)
Abstract Background Patients with advanced cancer often wish to be involved in medical decisions but may vary according to sociodemographic and clinical factors. This study examined how these variables relate to patients’ preferred roles in decision-making. Methods Data from 1198 advanced cancer patients were collected via self-administered questionnaires and clinical records. The Control Preferences Scale was used to classify patients into three profiles: Patient Control (decisions mainly made by the patient), Shared Control (decisions made jointly with the physician), and Physician Control (decisions primarily led by the physician). Associations with sociodemographic and psychological variables were analyzed. Results Among participants, 53% were in the Patient Control group, 10% in the Shared Control group, and 37% in the Physician Control group. Sociodemographic variables were significantly associated with decision-making profiles: men and participants with higher education (secondary or above) were more represented in the Physician Control group (41% and 43%), while women and unemployed participants predominated in the Patient Control group (both 57%). In contrast, clinical variables such as tumor site, treatment type, and disease stage showed no significant associations. Regarding psychological characteristics, the Physician Control group reported lower levels of distress and higher levels of positive adjustment (p <.05) compared to the other groups. Conclusion Decision-making preferences among advanced cancer patients depend predominantly on sociodemographic and psychological factors, rather than clinical variables. Patients deferring decisions to physicians experience lower distress and better psychological adjustment. Personalized communication informed by patient background and coping styles may improve patient-centered care and outcomes.